تقويم السيّاح لأبعاد جودة الخدمات الفندقية وعلاقتها ببعض المتغيرات دراسة ميدانية على نزلاء الفنادق في محافظة اللاذقية - طيوب, محمود; عبد الرحمن, نسرين; خضرة, سوزانا غازي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يشكل القطاع الفندقي أهمية كبيرة باعتباره أحد المقومات الأساسية لحركة السيّاحة, ورافداً أساسياً من روافد الاقتصاد الوطني, الأمر الذي يستوجب ضرورة إيلائه أهمية أكبر, وذلك من خلال تعزيز بنيته التحتية وتطوير كفاية الكوادر البشرية العاملة فيه. يهدف البحث الحالي إلى التعرف على آراء السيّاح وتقويمهم لأبعاد جودة الخدمات التي تقدمها الفنادق العاملة في محافظة اللاذقية, وعلاقتها ببعض المتغيرات المتمثلة بـ(جنس السائح, جنسيته, درجة الفندق, عدد مرات النزول), وبعد الدراسة والتحليل تمّ التوصل إلى النتائج التالية: - إن تقويم السيّاح لمستوى جودة الخدمات الفندقية بأبعادها المختلفة والمقدمة من قبل الفنادق التي تعاملوا معها هو تقويم جيد, ويتوافق مع المعايير العالمية لجودة الفنادق. - عدم وجود اختلاف بين السيّاح في تقويمهم لمستوى جودة الخدمات الفندقية المقدّمة لهم من قبل الفنادق التي تعاملوا معها تبعاً لمتغيرات جنس السائح وجنسيته وعدد مرات النزول في الفندق. - وجود اختلاف بين السيّاح في تقويمهم لمستوى جودة الخدمات الفندقية المقدّمة لهم من قبل الفنادق التي تعاملوا معها تبعاً لمتغير درجة الفندق, وهذه الفروق لصالح الفنادق من فئة أربع وخمس نجوم. The hotel sector is of great importance as it forms a main component of tourism. It is a key tributary in the national economy. This shows the need to devote even more attention to it by improving its infrastructure and raising the adequacy of human resources working in it. The current research aims at identifying tourists' views and their assessment of the dimensions of the quality of services provided by hotels in Lattakia, and its relation to some variables like the tourist gender, nationality, star rating, and number of checking in. After doing the research and analysis, we have reached the following results: - Tourists evaluation of the hotel services quality and its various dimensions provided by hotels is a good one, and it is in conformity with international standards of hotels quality. - There is no difference between the assessments of tourists and their recognition of the quality of hotel services provided to them by the hotels that they have dealt with according to the variables of sex and nationality and number of checking in and out, get off at the hotel. - There is a difference between tourists assessments and their recognition of the quality of hotel services provided to them by the hotels that they have dealt with according to the variable of star rating. These differences are in favour of four- and five-star hotels